Relationship between quiet eye and kinematic characteristics based on expertise in badminton backhand serve - Song, S.-H. (Perceptual and Motor Skills, 2025)
The badminton backhand serve is a fundamental skill that determines the start of a rally, requiring precise timing and stable movement control. In particular, effective visual attention, known as Quiet Eye (QE), is likely to play a crucial role in movement planning and motor control. However, research on QE during the execution of a badminton backhand serve remains limited. Therefore, this study aims to examine the differences in QE based on expertise while analyzing the interaction between QE and upper limb joint movements to understand the underlying mechanisms of the execution of the serve. By doing so, this study seeks to identify the specific visual information involved in badminton backhand serve performance and provide foundational data for performance enhancement. Expert and novice players were instructed to perform backhand short and long serves in both singles and doubles conditions, and QE, wrist joint MEA (Maximum Extension Angular Velocity), and elbow joint MEA were analyzed for each condition. The results showed that skilled players had a longer QE duration than novices, with a particularly longer QE and lower wrist MEA observed in the doubles short serve condition. Additionally, a significant correlation between QE and MEA was found during the execution of the short serve. These findings align with certain aspects of the posture-kinematics hypothesis, particularly in terms of joint-level control. However, further research incorporating direct measures of postural control is required, and there is a need for a more refined analysis of the relationship between visual attention and motor control in badminton serves.